Lactoferrin Knockout Mice Demonstrates Greater Susceptibility to Aggregatibacter actinomycetemcomitans–Induced Periodontal Disease. Issue 11 (1st November 2013) - Velusamy, S.K.; Ganeshnarayan, K.; Markowitz, K.; Schreiner, H.; Furgang, D.; Fine, D.H.; Velliyagounder, K.
Abstract : Background : Among the innate defense mechanisms in the oral cavity, lactoferrin (LF) is a vital antimicrobial that can modify the host response against periodontopathogens. Aggregatibacter actinomycetemcomitans is the main periodontopathogen of localized aggressive periodontitis. The aim of this study is to evaluate the role of LF during A. actinomycetemcomitans –induced periodontitis. Methods: Differences in the expression levels of cytokines, chemokines, chemokine receptors, and bone loss markers between wild‐type (WT) and LF knockout mice (LFKO −/− ) were evaluated by real time‐PCR. Serum IgG and LF levels were quantified by ELISA. Alveolar bone loss among the groups was estimated by measuring the distance from cemento‐enamel junction (CEJ) to the alveolar bone crest (ABC) at 20 molar sites. Results: Oral infection with A. actinomycetemcomitans increased LF levels in periodontal tissue ( P = 0.01) and saliva ( P = 0.0004) of wild‐type infected (WTI) mice compared to wild‐type control mice. Pro‐inflammatory cytokines such as interferon‐γ, tumor necrosis factor‐α, interleukin (IL)‐1β, IL‐6, and IL‐12 were increased in the infected LF knockout (LFKO −/− I) mice compared to the WTI mice, whereas the anti‐inflammatory cytokines IL‐4 and IL‐10 were decreased. Chemokines and chemokine receptors showed different expression patterns between WTI and LFKO −/− I mice. The LFKO −/− I mice developed increased bone loss ( P = 0.002), in conjunction with increased expression of receptor activator of nuclear factor‐κB ligand and decrease in osteoprotegerin, compared to WTI mice. Conclusions: These results demonstrate that the infected LFKO −/− mice were more susceptible to A. actinomycetemcomitans –induced alveolar bone loss, with different patterns of immune responses compared to those of WTI mice.